Effects of social distancing on psychological state and physical activity routines during the COVID-19 pandemic - Di Corrado, D.; Magnano, P.; Muzii, B.; Coco, M.; Guarnera, M.; De Lucia, S.; Maldonato, N. M. (Sport Sciences for Health, 2020)
Background: The novel coronavirus disease (COVID-19) has affected the entire world. Since the reporting of the first cases, Italy has quickly become the country hit second firmest in the world by the coronavirus. Governments` immediate protective restrictions modified the habit of the individuals and included full lockdowns of cities, travel, restricted social congregations, and suspended schools. Objectives: The aim of this study was to survey the general community in Italy to better recognize their levels of psychological impact, emotional responses and maintaining their daily exercise or physical activity routines during the initial stage of the COVID-19 outbreak. Methods: 670 adults were invited to complete an online survey collecting information on demographic data, physical and emotional symptoms in the past 14 days, contact history with COVID-19, and keeping regular physical activity. Data analysis was conducted through mixed qualitative and quantitative methods. Results: During the initial phase of the COVID-19 outbreak in Italy, more than half of the respondents reported a significant psychological and physical impact. Conclusion: The COVID-19 pandemic is bringing significant challenges to people, families, and countries. For further studies, these findings can be used to advance psychological interventions to reduce the consequences of the COVID-19 pandemic.